DakhÃ®l al-IsrÃ¢âilÃ®yÃ¢t Kisah Nabi YÃ»suf dalam al-JÃ¢miâ li AhkÃ¢m al-QurâÃ¢n Karya al-QurtubÃ® - Amrullah Hafizh, Azhar (Mutawatir, 2015)
Normatively, the Prophet Muhammad is not giving a ban to tell tales originating from the BanÃ® IsrÃ¢âÃ®l. The Prophet simply gave the record that his people did not justify and deny the stories narrated by Ahl al-KitÃ¢b. However, in the course of the history of Islam, many isrÃ¢âilÃ®yÃ¢t seeps into some sort of authoritative books of JÃ¢miâ al-BayÃ¢n created by al-TabarÃ®, TafsÃ®r al-QurâÃ¢n al-âAzÃ®m by Ibn KathÃ®r, RÃ»h al-MaâÃ¢nÃ® by al-AlÃ»sÃ®, and al-JÃ¢miâ li AhkÃ¢m al-QurâÃ¢n by al-QurtubÃ®. Ironically, in many cases, isrÃ¢âilÃ®yÃ¢t that goes into the book of commentary of the Koran without any comments from the authors, so it assumes that the isrÃ¢âilÃ®yÃ¢t is a strong opinion and can be used as a reference. As a result, isrÃ¢âilÃ®yÃ¢t like virus that continues to undermine the authenticity of the Koran